Numerical simulation of adhesively-bonded T-stiffeners by cohesive zone models - Ferreira, J.A.M. (2022)
30th International Conference on Flexible Automation and Intelligent Manufacturing (FAIM2021) -15-18 June 2021, Athens, Greece